Korelasi Kadar Adiponektin dengan Kadar Kolesterol High Density Lipoprotein pada Penyandang Obes - Mulya, Fiona Septi; Efrida, Efrida; Rofinda, Zelly Dia (Jurnal Kesehatan Andalas, 2021)
Adiponectin and HDL cholesterol have a protective cardiovascular effect. Adiponectin levels decrease in obese people. This causes ATP-binding cassette transporter A1 expression and apolipoprotein A-I synthesis in hepatocytes to decrease, resulting in impaired HDL cholesterol synthesis. Objectives: To determined the correlation between adiponectin levels with HDL cholesterol levels in obese. Methods: This was the analytic study with a cross-sectional design of 59 obese people who met inclusion and exclusion criteria at RSUP dr. M. Djamil Padang, from January to August 2019. Research subjects were grouped into two groups based on WHO Asia Pacific body mass index (BMI) classification. First-degree obesity group (25.0 Â£ BMI <30.0 kg/m2) and second-degree obesity group (BMI â‰¥ 30.0kg/ m2). Adiponectin levels were examined by the enzyme-linked immunosorbent assay (ELISA) method and HDL cholesterol levels by the enzymatic colorimetric method. Data analyzed by Pearson correlation test, significant if p <0.05. Results: Research subjects 59 people (17 men, 42 women), average age 35 (8.04) years. Adiponectin levels in the first-degree obesity group were higher than second-degree obesity group, with a mean difference between groups 1.03 Î¼g/mL (CI: 95%: 0.14 - 1.92, p = 0.02). Results showed adiponectin levels positively correlated with HDL cholesterol levels of moderate strength (r = 0.45) and statistically significant (p = <0.001). The results of the population subanalysis show relatively similar patterns. First-degree obesity population (r = 0.55; p = 0.002), second-degree obesity population (r = 0.41; p = 0.026). Conclusions: Adiponectin levels correlate with HDL cholesterol levels.Keywords: adiponectin, HDL cholesterol, obesity